Domestication Impacts the Wheat-Associated Microbiota and the Rhizosphere Colonization by Seed- and Soil-Originated Microbiomes, Across Different Fields - Abdullaeva, Yulduzkhon; Ratering, Stefan; Ambika Manirajan, Binoy; Rosado-Porto, David; Schnell, Sylvia; Cardinale, Massimiliano (Frontiers in Plant Science, 2022)
The seed-transmitted microorganisms and the soil microbiome in which the plant grows are major drivers of the rhizosphere microbiome, a crucial component of the plant holobiont. The seed-borne microbiome can be even co-evolved with the host plant as a result of adaptation and vertical transmission over generations. The reduced genome diversity and crossing events during domestication might have influenced plant traits important for root colonization by seed-borne microbes as well as rhizosphere recruitment of microbes from the bulk soil. However, the impact of the breeding on seed-transmitted microbiome composition and the plant ability of microbiome selection from the soil remain unknown. Here, we analysed both endorhiza and rhizosphere microbiome of two couples of genetically related wild and cultivated wheat species (Aegilops tauschii/Triticum aestivum and T. dicoccoides/T. durum) grown in three locations, by using 16S rRNA gene and ITS2 metabarcoding, in order to assess the relative contribution of seed-borne and soil-derived microbes to the assemblage of the rhizosphere microbiome. We found more bacterial and fungal ASVs transmitted from seed to the endosphere of all species compared to the rhizosphere, and these transmitted ASVs were species-specific regardless of location. Only in one location, more microbial seed transmission occurred also in the rhizosphere of A. tauschii compared to other species. Concerning soil-derived microbiome, the most distinct microbial genera occurred in the rhizosphere of A. tauschii compared to other species in all locations. The rhizosphere of genetically connected wheat species was enriched with similar taxa, differently between locations. Our results demonstrate that host plant criteria for soil bank’s and seed-originated microbiome recruitment depend on both plants' genotype and availability of microorganisms in a particular environment. This study also provides indications of co-evolution between the host plant and its associated microbiome resulting from the vertical transmission of seed-originated taxa.